Introduction - Gardikas, Katerina (The Historical Review/La Revue Historique, 2021)
This collection of articles was conceived long before the outbreak and worldwide spread of Covid-19. It was intended as a review of recent trends in the writing of modern medical history in Greece thanks to the broader social relevance of public health history. While it still represents current ideas on the history of health and medicine among its Greek practitioners, it appears, nonetheless, at a time when public opinion has put the notions of public health, contagion and governance into sharp relief as societies are being overwhelmed by insecurity and a primal sensation of fear. Thus, public health and social medicine have entered the historiographical limelight.